Stress and Coping: An Economic Approach - Klaus Wälde; Niklas Scheuer (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We present a psychological model of stress. Appraisal translates stressors into subjective stress. Stress reduces instantaneous utility of an individual directly and via cognitive load. Coping can be under the control of the individual or more automatic. We predict the occurrence of uncontrolled coping .emotional outbursts .as a function of an individuals theory-consistent personality and environment. We explain when stressors reduce income. We also explain under which conditions rising income does not go hand in hand with rising stress. First steps towards a theory of therapy show how stressed individuals can improve their well-being beyond standard coping measures.
Keywords: D03; D91; I12; 330; Stress; coping; personality; controlled vs. automatic reaction; emotional outbursts; income